2008
DOI: 10.1039/b804911d
|View full text |Cite
|
Sign up to set email alerts
|

Detecting bacteria and determining their susceptibility to antibiotics by stochastic confinement in nanoliter droplets using plug-based microfluidics

Abstract: This article describes plug-based microfluidic technology that enables rapid detection and drug susceptibility screening of bacteria in samples, including complex biological matrices, without pre-incubation. Unlike conventional bacterial culture and detection methods, which rely on incubation of a sample to increase the concentration of bacteria to detectable levels, this method confines individual bacteria into droplets nanoliters in volume. When single cells are confined into plugs of small volume such that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
397
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(411 citation statements)
references
References 45 publications
2
397
0
5
Order By: Relevance
“…In addition to compartmentalizing reactions, droplet-based microfluidics can also be used to encapsulate prokaryotic [14][15][16][17][18] and eukaryotic cells [19][20][21][22][23], and even the embryos of multicellular organisms [24,25], which opens up a new avenue for cell analysis. Recently, Brouzes et al [19] developed a droplet-based viability assay that permitted quantitative analysis of cell viability and growth within compartmentalized aqueous droplets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to compartmentalizing reactions, droplet-based microfluidics can also be used to encapsulate prokaryotic [14][15][16][17][18] and eukaryotic cells [19][20][21][22][23], and even the embryos of multicellular organisms [24,25], which opens up a new avenue for cell analysis. Recently, Brouzes et al [19] developed a droplet-based viability assay that permitted quantitative analysis of cell viability and growth within compartmentalized aqueous droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Shortening the diagnosis time to identify specific antibiotics to treat bacterial infections could decrease the patient mortality, and reduce the cost of patient treatment. Boedicker et al [60] described a plug-based microfluidic technique that enabled to characterize the drug sensitivity of bacteria in samples and measure the minimal inhibitory concentration of antibiotics. By confining the cells in nanoliter droplets, the cell density was increased without preincubation and the time required to detect the bacteria was reduced.…”
Section: Droplet Mode High-throughput Screeningmentioning
confidence: 99%
“…The optical detection of fluorescence signal is commonly performed in a serial manner, where drops are injected into a funnelshaped microchannel consisting of a narrow constriction which forces the drops to arrange in a single file, and to ensure that drops enter the detection region one at a time. [2][3][4][5][6]9,10 We have recently shown that the throughput of the serial interrogation process is limited by the rate at which droplets become unstable and undergo undesirable break-up as they flow through the constriction. 11 To achieve a droplet break-up rate of less than 1%, the maximum throughput was approximately 7000 drops s −1 for 40 pL drops.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It is now possible to generate and manipulate droplets at kilohertz speeds. 8 In many biochemical assays, fluorescence is used as a read-out for the reactions occurring inside the drops, and can indicate the presence of cells or molecules of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation